Mapping of Agriculture Research Output in Sri Lanka: A Scientometric Analysis - Maheswaran, R. (Indian Journal of Information Sources and Services, 2016)
The study examines Sri Lanka’s performance based on its publication output in Agriculture during 1989–2015, based on several parameters, including the year wise growth, national publication output and impact in terms of average citations per paper, international collaboration output and share and contribution of major collaborative partners, contribution, impact of select top 15 Sri Lanka institutions and select top 15 most productive authors, patterns of communication in national and international journals. The study uses 27 years (1989–2015) publications data in dental sciences of India and other countries drawn from Web of Science international multidisciplinary bibliographical database.